Learning system suspension using e-module in vocational education with model 4D - Sigit Purnomo; Arif Bintoro Johan; Ega Bimantara; Dianna Ratnawati; Afri Yudantoko; Abdullah Syafiq (Universitas Sarjanawiyata Tamansiswa, 2022)
The results of this study (1) determine how much influence the use of the E-Module suspension system has to improve student achievement. (2) Knowing the eligibility level of the E-module used in the learning process of the suspension system. (3) Knowing students' responses to E-Module-based learning media about the suspension system. The e-module development uses a 4-D model (Define, Design, Develop, Dissemination). The electronic learning module was validated by two material experts and one media expert and then tested on 5 students for small-scale trials and 26 students for large-scale students of class XI majoring in Automotive Light Vehicle Engineering, SMK Muhammadiyah Semin. Data collection used a four-scale Likert scale questionnaire. choice. The feasibility of electronic learning modules can be seen from the results of material validation, media validation and testing of students to get proper results. The results of e-module development from material validation and expert validation as well as dissemination to students state that the e-module is in the very feasible category. So it can be concluded that the use of suspension e-modules is feasible for vocational learning